Resonance modulation vibration mechanism of equally-spaced planetary gearbox with a localized fault on sun gear. (1st March 2022) - Xu, Lei; Ding, Kang; He, Guolin; Li, Yongzhuo; Chen, Zhuyun
Highlights: Response model of planetary gearbox with a localized fault on sun gear are built. Resonance modulation mechanism is deduced theoretically. Internal interaction of gear system is considered. Resonance modulation sidebands are closely related to impacts. A new sight is given for the diagnosis about the localized fault on sun gear. Abstract: The vibration signal of the planetary gearbox shows complicated modulation sidebands no matter the gear is normal or fault. It leads to a challenge in the fault diagnosis, especially for the localized faults which stimulate resonance modulation phenomena. To reveal the resonance modulation mechanism of sun gear's localized fault, the vibration signal model is built based on the convolution of transient impact force and transfer function of the planetary gearbox. Three prominent transfer paths including modal parameters of the flexible ring gear or housing are involved to obtain resonance modulation sidebands. A projection function is used to model the time-varying direction of transient impact force. Resonance modulation sidebands of a single planet gear meshing is first deduced, and then the sidebands related to multiply planet gears meshing. The resonance modulation of localized fault on sun gear are concluded to be consist of three groups of sidebands. The proposed model is verified by the good consistency between simulation and experimental testing on a commodity planetary gearbox. It contributes an important and effective frequency indicator to confirm the condition of planetary gearboxes.